APPROXIMATE METHOD FOR AN INITIAL VALUE PROBLEM FOR IMPULSIVE DIFFERENCE EQUATIONS - Madamlieva, Ekaterina; Kasmska, Loreta; Hristova, Snezhana (Matematichki Bilten, 2017)
An algorithm for constructing two monotone sequences of upper and lower solutions of the initial value problem for nonlinear impulsive difference equations is given. It is proved that both functional sequences are convergent and their limits are minimal and maximal solutions of the considered problem. Theoretical results are ilustrated by an example.